Spiritual development from the perspective of consciousness. Outline of the problem - Wysocki, Adam (Filozofia Chrześcijańska, 2019)
The article focuses on the issue of spiritual development from the perspective of consciousness. The question of spiritual development exists in close connection with the concept of spirituality. The issue of consciousness can be reduced to three elements that make up a single act of consciousness: an empirical subject, complementing the object, and a non-act self-awareness, i.e. a non-empirical or proper subject. Self-awareness plays a key role in spiritual development in the fi eld of consciousness. The development of self-awareness should strive to reveal non-act self-awareness, but it has a similar structure and is experienced like any other acts of awareness. Spiritual development is the process of the of self-awareness growth and the constitution of the “Self” as an empirical subject that separates itself from a specifi c class of objects that are a component of the fi eld of possible experience for a person. The eff ects of spiritual development can also be described as self-knowledge, which can be a conceptual explanation of either actual experiences or a more stable state of the human subject.